O regime jurídico da dúvida razoável na valoração aduaneira - Pereira, Cláudio Augusto Gonçalves (2025)
This doctoral thesis focuses on the legal framework for reasonable doubt in customs valuation. Given the scenario in which divergent and incomplete practices still prevail in the application of transaction value, this thesis has the general objective of analyzing the positive experiences of customs valuation in South American countries, in order to identify practices that, by more faithfully adhering to the principles of the Customs Valuation Agreement (AVA-GATT), promote greater transparency, legal certainty and alignment with the best international trade practices. The problem to be answered is: “Does the Brazilian system provide for a reasonable doubt procedure in customs control that can achieve the correction of the value declared by the importer before customs with respect to the fundamental rights and guarantees contained in the international agreement itself? Are there reasonable deadlines for the exercise of the public administration's right to doubt? Is there national uniformity in the exercise of the right to doubt by Brazilian customs?” The research will be carried out through the analysis of documents, as well as a bibliographic review. The records will be related to bibliographic and documentary research, composing a triangulation of data sources, in order to cross-reference them for interpretation, supporting the research. As a result, it can be stated that the hypothesis was proven, given that the behavior of Brazilian customs administrations often reveals a practice that disregards the primacy of the transaction value. In many cases, customs authorities reject the declared value claiming that it is "ostensibly high or low", without presenting an objective criterion to substantiate this decision, transferring to the importer the responsibility for justifying the declared value. Within this context, the Customs Valuation Agreement (AVA-GATT) does not authorize the rejection of transaction values based on subjective adjectives such as "high" or "low" without a solid justification. To this end, the AVA-GATT provides that the customs administration operates with a presumption of veracity and good faith in the data provided by the importer, with the latter initially only having the duty to present supporting documents, such as a commercial invoice, transport contract and insurance policy, which prove the declared value